LIX1 regulates YAP1 activity and controls the proliferation and differentiation of stomach mesenchymal progenitors. Issue 1 (December 2016) - McKey, Jennifer; Martire, Delphine; de Santa Barbara, Pascal; Faure, Sandrine
Abstract Background Smooth muscle cell (SMC) plasticity maintains the balance between differentiated SMCs and proliferative mesenchymal progenitors, crucial for muscular tissue homeostasis. Studies on the development of mesenchymal progenitors into SMCs have proven useful in identifying molecular mechanisms involved in digestive musculature plasticity in physiological and pathological conditions. Results Here, we show thatLimb Expression 1 (LIX1 ) molecularly defines the population of mesenchymal progenitors in the developing stomach. Using in vivo functional approaches in the chick embryo, we demonstrate thatLIX1 is a key regulator of stomach SMC development. We show thatLIX1 is required for stomach SMC determination to regulate the expression of the pro-proliferative geneYAP1 and mesenchymal cell proliferation. However, as stomach development proceeds, sustainedLIX1 expression has a negative impact on further SMC differentiation and this is associated with a decrease in YAP1 activity. Conclusions We demonstrate that expression of LIX1 must be tightly regulated to allow fine-tuning of the transcript levels and state of activation of the pro-proliferative transcriptional coactivator YAP1 to regulate proliferation rates of stomach mesenchymal progenitors and their differentiation. Our data highlight dual roles for LIX1 and YAP1 and provide new insights into the regulation of cell density-dependent proliferation, which is essential for the development and homeostasis of organs.